Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) Terrhadap Minat Belajar IPA Siswa Madrasah Ibtidaiyah Swasta (MIS) As’Adiyah Kabupaten Wajo - Mu'thy, Abdul (AIJER: Algazali International Journal Of Educational Research, 2025)
This study aims to analyze the effect of implementing the Problem-Based Learning (PBL) model on students’ learning interest at Madrasah Ibtidaiyah Swasta in Belawa Subdistrict, Wajo Regency. The research employed a quantitative approach with an experimental research design, specifically a pre-experimental design using the one-group pretest-posttest model. The study involved two variables: the independent variable, namely the implementation of the PBL learning model, and the dependent variable, namely students’ learning interest. The population of this study consisted of all fourth-grade students at Madrasah Ibtidaiyah Swasta in Belawa Subdistrict, Wajo Regency, totaling 257 students. The research sample comprised 41 fourth-grade students who were selected as the participants. The instruments used in this study were a student learning interest questionnaire and an observation sheet on the implementation of the PBL model, both of which had been validated by experts (validators). The collected data were analyzed using descriptive statistics and inferential statistics to test the research hypothesis. The results revealed that the implementation of the Problem-Based Learning model had a significant effect on students’ interest in learning science at Madrasah Ibtidaiyah Swasta in Belawa Subdistrict, Wajo Regency. Based on the hypothesis testing, a significance value of 0.003 < 0.05 was obtained, indicating that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that there was a significant difference in students’ learning interest before and after the implementation of the Problem-Based Learning model.